Comparing Translation Strategies of Two Different Translators of 'Tintin In Tibet' - Theresia Lunetta Thionarto; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2020)
This study discusses the differences in Indonesian translations of Tintin in Tibet published by two different publishers. The translation strategies used in these books were qualitatively analyzed using the theory of Mona Baker (2018). The rank of the most dominant strategies, from the most frequent to the less, used by the translators are paraphrase using the unrelated word, paraphrase using the related word, cultural substitution, omission, and less expressive word. The naturalness of the translation is affected by the strategies and by the traits of the character and context. In the translation of swear words, the best strategy used to translate the swear words are cultural substitution. It is better than other strategies because the readers can understand more if familiar swear words are used. In conclusion, both translators have different results of natural translation, but in the translation of swear words, the translator of Indira provides more natural translation.Keywords: Translation, translation strategies, natural, swear words